Spirituality and mental training as predictors of athletic resilience - Blessy Bel T. Palma Gil; Arvin Andacao (spdfharmony.com, 2025)
Background of study: The interplay between spirituality and mental training in enhancing sports resilience remains underexplored, particularly in the Philippine context. Aims: This study aimed to examine the predictive influence of spirituality and mental training on the sports resilience of athletes. Methods: A quantitative correlational design, specifically employing predictive modelling through multiple regression analysis, was used. A total of 145 student-athletes, identified using the Raosoft sample size calculator, participated in the study out of 231 varsity athletes in Davao Oriental during the Mindanao sports competition. Descriptive, correlation, and regression analyses were conducted to identify the levels, relationships, and predictors of athletic resilience. Results: The findings revealed that the overall levels of spirituality, mental training, and resilience in sports were all very high. The spirituality and mental training were strongly correlated with sports resilience. Among the subscale indicators, spiritual well-being, locus of control, performance skills, and mental imagery significantly predicted athletic resilience. Conclusion: The study concluded that spiritual and mental training components significantly contribute to the development of sports resilience among athletes. It is recommended that athletic programs integrate spiritual well-being and targeted mental skill strategies to strengthen resilience in competitive settings.